Optimizing School Principals' Leadership through an Agile Organization Approach for Sustainable School Development - Siti Komara; Azhar Affandi; Horas Djulius (Glosains: Jurnal Sains Global Indonesia, 2026)
Background: The rapid and uncertain dynamics of the BANI (Brittle, Anxious, Non-linear, and Incomprehensible) era require schools to develop adaptive leadership models to achieve sustainable institutional development. Traditional leadership approaches often face challenges in responding to complex educational changes, technological demands, and organizational uncertainties. Objective: This study aims to examine the optimization of school principals’ leadership through an Agile Organizationapproach to support sustainable school development. Methods: This study employed a qualitative case study approach at Ibnu Khaldun Islamic School Cirebon. Data were collected through observations, interviews, focus group discussions, and documentation involving foundation administrators, school principals, teachers, and education staff. Data analysis was conducted using thematic analysis, IFAS-EFAS analysis, the TOWS Matrix, and strategic analysis. Results: The findings indicate that the implementation of school principals’ leadership roles based on the EMASLIM framework has not been fully optimized, particularly in strengthening innovation, collaboration, digital transformation, and continuous improvement. The application of Agile Organization principles remains limited in terms of establishing a shared vision, empowering teams, facilitating adaptive decision-making, promoting organizational learning, and utilizing technology effectively. The main challenges include limited leadership competencies, insufficient training opportunities, weak communication systems, inadequate infrastructure, and unclear organizational regulations. Strategic analysis recommends SO strategies that focus on leadership transformation, governance strengthening, human resource development, technology integration, learning quality improvement, and partnership expansion. Conclusion: Optimizing school principals’ leadership through an Agile Organization approach can strengthen school adaptability, innovation capacity, and sustainable development. This study contributes to educational management by integrating agile principles into school leadership practices to address contemporary educational challenges.